Nesting and foraging behavior of Xylocopa valga in the Ejina Oasis, China - He, Chunling; Zhu, Chaodong (PloS one, 2020)
Xylocopa valga is extinct in Latvia and Lithuania and is critically endangered in Poland, and its distribution in the Ejina Oasis, China, is currently unknown. Studies on the biology of X. valga are scarce, and thus, conservation efforts for this species are currently limited. Here, we investigated the morphological characteristics, nest architecture, nest structure and food type of offspring in the nest cells of X. valga. This research was conducted in the Populus euphratica forest reserve in the Ejina Oasis, China, between July 2014 and June 2019. The primary investigation methods included visual inspection, photography, observation and measurements of nest anatomy, and examination of pollen stores by microscopy. We found that in the Ejina Oasis, China, X. valga builds its nests in the dead wood of P. euphratica. X. valga is univoltine. Its lifestyle varies from solitude to symbiosis. When many females nest near each other, several females may share a single nest entrance, based on which they build their own cells. The nests are branched. According to our results, there is a significant difference between the thickness of the inner cell partition and that of the outermost cell partition in the branched tunnel. In the P. euphratica forest area, the food for the progeny of X. valga is mainly composed of the pollen and nectar of Sophora alopecuroide and Populus euphratica. Therefore, X. valga and S. alopecuroides exhibit close ecological interactions in the P. euphratica forest ecosystem.